Nationalism, urban poverty and identity in Maputo, Mozambique - Sumich, Jason (2010)
This paper examines the changing perceptions of Frelimo's nationalist project amongst members of the middle class in Maputo, Mozambique's capital. I argue that nationalism in Mozambique created a system of meaning and new forms of identity that are especially relevant for more privileged urbanites. However, growing urban poverty and inequality has had an effect throughout the social spectrum in Mozambique. The self-same set of nationalist values provides a critique for the failings of the regime as everyday life continually conflicts with the government's message of unity and progress for all and this is causing a loss of support even among the regime's beneficiaries.
Keywords: G - Mozambique / Moçambique; L - english / inglês; urbanization / urbanização